A Scientific Review of Recycling Practices and Challenges for Autoclaved Aerated Concrete in Sustainable Construction - Shuxi (Hiro) Wang; Guomin Zhang; Chamila Gunasekara; David Law; Yongtao Tan; Weihan Sun (Buildings, 2025)
Autoclaved Aerated Concrete (AAC) is a lightweight, thermally insulating, and fire-resistant building material that has become prominent in sustainable construction due to its reduced production energy demands and minimal environmental impact. As an increasing number of AAC-based structures reach end-of-life, the effective recycling and reuse of AAC waste present both challenges and opportunities within the context of sustainable building practices and circular economy frameworks. This study presents a scientometric review of AAC recycling research published between 2014 and 2024, using the Web of Science database and bibliometric tools such as CiteSpace. Key trends, techniques, and knowledge gaps in AAC recycling are identified, highlighting issues such as high energy consumption, limited practical implementation, and the absence of standardized recovery protocols. The study also outlines emerging research pathways, including detailed material characterization, development of recycling standards, innovative reuse techniques, hybrid material systems, and the integration of recycled AAC in new construction. These insights provide a foundation for advancing sustainable building material strategies and inform policy and practice in construction waste management.